HUBUNGAN TINGKAT KONSUMSI PROTEIN DAN PRAKTIK CUCI TANGAN PAKAI SABUN PADA BALITA STUNTING USIA 24-59 BULAN DI WILAYAH PESISIR - Joyeti Darni (JURNAL SVASTA HARENA RAFFLESIA, 2026)
Stunting not only affects physical growth but also children's cognitive development and health, which impacts the nation's future productivity and competitiveness. One of the most direct causes of stunting is insufficient protein intake. Children in coastal areas under the age of five are significantly affected by household food security. Children from fishing families often consume small fish because their parents prefer to sell their catch of large fish, while small fish are for their own consumption. Even unsalable fish are sometimes eaten by the family. The aim of the study was to determine the relationship between protein consumption levels and handwashing practices with soap and the nutritional status of short and very short toddlers aged 24-59 months in coastal areas. This research method used a cross-sectional research design, the research subjects were 54 stunted toddlers living in the coastal areas of Lombok Island. The results showed that the gender was almost equal between boys (48.1%) and girls (51.9%), with stunted toddlers as many as 79.6% and very short 20.4%. The level of protein adequacy of toddlers was in the good category (37.0%) and above adequacy (42.6%). The practice of washing hands with soap was the majority of toddlers, 53.7% of whom washed their hands with soap. The conclusion of the study was that there was no significant relationship (p>0.05) between the level of protein consumption and handwashing behavior with the nutritional status of stunted and very short children.